Laparoscopic mirror cholecystectomy: gallbladder lithiasis in a patient with situs inversus - Castro Sosa, Monica; Hernandez Sosa, Reyger; González, Yazmin G. (International Journal of Research in Medical Sciences, 2024)
The location of the organs with respect to the midline of the body is known as situs, situs inversus refers to the sagittal inversion of the thoracoabdominal organs with an incidence of 0.01% of the population. A 51-year-old female with a history of SIT, refers colic in the left hypochondrium associated with the intake of cholecystokinetic food, vesicular lithiasis is diagnosed by ultrasound, laparoscopic cholecystectomy was performed with placement of 12 mm trocars in the umbilical and subxiphoid region slightly lateralized to the left, 5 mm trocars below the costal margin left midclavicular line and on the left flank anterior axillary line. Deletion of the Pitx2 transcription factor disrupts normal morphogenesis and develops visceral asymmetry. The risk of developing gallstones is the same as the rest of the population; which presents classic symptoms, 30% will present epigastric pain, 10% will present pain in the right hypochondrium and the rest will present pain in the left upper quadrant, laparoscopic cholecystectomy is the gold standard treatment. In this genetic anomaly, it is important to know the changes in the clinical presentation for a timely diagnosis. Modifications in the technique and anatomical arrangement represent a challenge for the surgical team, which is why an experienced team with extensive knowledge of biliary anatomy is required to avoid the risk of injury. Cation of the organs with respect to the midline of the body is known as situs, situs inversus refers to the sagittal inversion of the thoracoabdominal organs with an incidence of 0.01% of the population, 1/10,000-20,000 births. A 51-year-old female with a history of SIT, refers colic in the left hypochondrium associated with the intake of cholecystokinetic food, vesicular lithiasis is diagnosed, laparoscopic cholecystectomy was performed with placement of 12 mm trocars in the umbilical and subxiphoid region slightly lateralized to the left, 5 mm trocars below the costal margin left midclavicular line and on the left flank anterior axillary line. Conventional mirror cholecystectomy was performed. Deletion of the Pitx2 transcription factor disrupts normal morphogenesis and develops visceral asymmetry. The risk of developing gallstones is the same as the rest of the population; which presents classic symptoms, 30% will present epigastric pain, 10% will present pain in the right hypochondrium and the rest will present pain in the left upper quadrant, laparoscopic cholecystectomy is the gold standard treatment for surgical resolution, the main change in the surgical technique is the placement of the trocars. In this genetic anomaly, it is important to know the changes in the clinical presentation for a timely diagnosis. Modifications in the technique and anatomical arrangement represent a challenge for the surgical team, which is why an experienced team with extensive knowledge of biliary anatomy is required to avoid the risk of injury.